Pelatihan Tata Kelola Pariwisata dengan Pendekatan CHSE bagi Pelaku Perhotelan di Kota Medan - Liyushiana; Agustinus Denny (Jurnal Abdimas Pariwisata, 2022)
Tourism Governance Training with CHSE Approach for Hospitality Actors in Medan City Tourism governance training with the CHSE approach is expected to be able to provide solutions for hoteliers in order to implement the health and safety standards recommended by the government in the accommodation and hospitality sector. The method used in community service in the form of this training is the classroom method and field study. The classroom method is used to introduce basic theories related to tourism development and the basic principles of CHSE in the hotel industry, while the field study technique is carried out by inviting training participants to visit Roemah 28 which is one of the most popular accommodation facilities in Medan City. The purpose of this field study is to provide a practical arena for implementing the CHSE directly in the field. The results obtained indicate an increase in the knowledge and enthusiasm of the trainees to implement CHSE in the field. In the future, follow-up activities are also needed, in the form of monitoring the extent to which training participants have implemented the CHSE and what obstacles they encountered